EDUKASI PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA SISWA KELAS 3 MI ASHABUL MAIMANAH MELALUI DEMONTRASI DAN MEDIA AUDIO VISUAL - Hamidah Hamidah; Nugrahini Kusumawati; Helmalia Putri; Diana Dwi Yuliani; Ima Pujiawati (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
One crucial aspect that supports the health of the individual body as a whole is oral and dental health, because healthy teeth have an impact on overall body health. Teeth and mouth problems will have an impact on the overall condition of the body, therefore dental health problems require handling and attention from each individual in this case, especially school-age children. However, not a few elementary school children experience many dental errors, especially cavities. So that the purpose of this community service activity is to provide education on dental and oral health maintenance for elementary school students. The selected partners were 40 class III students of MI Ashabul Maimanah. The activity took place by providing counseling in the form of demonstrations and audio visuals. After counseling, students were asked to practice how to brush their teeth and asked to fill out a questionnaire sheet. The result of this activity was that 92.5% of students were classified as good at understanding the importance of brushing their teeth and 85% of students considered brushing their teeth fun. Furthermore, the results of tooth brushing practice are known to 90% of students can brush their teeth properly and correctly